High Expression of Pyruvate Kinase M2 is Associated with Chemosensitivity to Epirubicin and 5-Fluorouracil in Breast Cancer - Lin, Yang (J Cancer, 2015)
Background: Pyruvate kinase M2 (PKM2) is the key enzyme in the Warburg effect, and it was recently reported to be involved in the metabolic pathways of chemotherapeutic drugs. However, the role of PKM2 in breast cancer and its influence in the sensitivity to front-line anticancer drugs remains unclear. Methods: In this study, we examined the correlation between the expression of PKM2 and the sensitivity of primary breast cancer cells to anticancer drugs. PKM2 expression was studied by immunohistochemistry using biopsy samples of 296 patients diagnosed with invasive breast carcinoma, and the collagen gel droplet embedded culture-drug sensitivity tests (CD-DST) was conducted to all the patients to detect in vitro chemosensitivity after surgery. Results: We found high PKM2 expression was significantly associated with in vitro chemosensitivity to epirubicin (EPI) (P=0.019) and 5-fluorouracil (5-Fu) (P=0.009) in breast cancer patients. Then we used a small group of neoadjuvant chemotherapy cases to confirm that the higher PKM2 expression, the better pathological response to therapy was obtained in patients treated with EPI-based or EPI plus 5-Fu chemotherapy regimens. Although univariate and multivariate analysis indicated that high PKM2 was a poor independent predictor of progression free survival (PFS) and overall survival (OS) in breast cancer, patients with PKM2 high expression who received EPI-based or EPI plus 5-Fu chemotherapy were found to have a longer PFS (P=0.003, P=0.013) and OS (P=0.003, P=0.004) than patients treated with non-EPI/5-Fu-based regimens, respectively. Conclusions: Our findings confirmed the poor prognosis of high PKM2 expression in breast cancer patients and revealed the predictive value of high PKM2 in the therapeutic response to EPI and 5-Fu. Moreover, our results provide the guidance of individual treatment for breast cancer patients who are foreboded a poor prognosis by the presence of high PKM2 status.